Cracking the code: Investigating the relationship between big five personality traits and stem education - Rashidin Idris; Juppri Bacotang; Priyalatha Govindasamy; Suppiah Nachiappan (Human Resource Management Academic Research Society (HRMARS), 2023)
The ultimate objective of this research is to provide light on the complex relationship between Big Five personality traits and jobs in science, technology, engineering, and mathematics (STEM). This study examines the role of personality traits, notably openness, conscientiousness, extraversion, agreeableness, and neuroticism, in growing one's interest and proclivity for STEM careers by examining data from a large sample of studies. The study's findings have far-reaching implications for both individuals and society as a whole. Understanding the influence of personality traits on STEM career pursuits can assist educational institutions, career counsellors, and policymakers in creating environments that encourage and support persons with specific personality profiles to pursue STEM jobs. Individuals can also gain substantial insights into their own predispositions and aptitudes, allowing them to make informed career decisions that are aligned with their own personality traits. By cracking the code and unravelling the deep relationship between Big Five personality traits and STEM career choices, this research hopes to contribute to the greater goal of broadening and strengthening the STEM workforce, ultimately paving the way for a more inclusive and innovative future